Air–sea gas exchange in a seagrass ecosystem – results from a 3He ∕ SF6 tracer release experiment - R. Dobashi; D. T. Ho (Biogeosciences, 2023)
Seagrass meadows are some of the most productive ecosystems in the world and could help to mitigate the increase of atmospheric CO2 from human activities. However, understanding the role of seagrasses in the global carbon cycle requires knowledge of air–sea CO2 fluxes and hence knowledge of the gas transfer velocity. In this study, gas transfer velocities were determined using the 3He and SF6 dual tracer technique in a seagrass ecosystem in south Florida, Florida Bay, near Bob Allen Keys (25.02663∘ N, 80.68137∘ W) between 1 and 8 April 2015. The observed gas transfer velocity, normalized for CO2 in freshwater at 20 ∘C, k(600), was 4.8 ± 1.8 cm h−1, which was lower than that calculated from published wind speed/gas exchange parameterizations. The deviation in k(600) from other coastal and offshore regions was only weakly correlated with tidal motion and air–sea temperature difference, implying that wind is the dominant factor driving gas exchange. The lower gas transfer velocity was most likely due to wave attenuation by seagrass and limited wind fetch in the study area. A new wind speed/gas exchange parameterization is proposed (k<mfenced close=")" open="(">600</mfenced>=0.143<msubsup>u102</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="91pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="04f1895a53c6ecaeaf8f8e235a55f34e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-20-1075-2023-ie00003.svg" width="91pt" height="17pt" src="bg-20-1075-2023-ie00003.png"/></svg:svg>), which might be applicable to other seagrass ecosystems and wind-fetch-limited environments.